2019
DOI: 10.33828/sei.v30.i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Professional Development Focused on Promoting Effective Implementation of the Next Generation Science Standards

Abstract: The purpose of this study was to examine the design, implementation, and initial outcomes of a collaborative professional development program intended to prepare middle and high school educators to implement effectively the Next Generation Science Standards (NGSS) in classrooms with diverse learners. The professional development program discussed herein was designed by a university in partnership with a local school district and incorporated key principles of effective professional development associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…While teachers in the current study were frustrated by a strict compliance model through the implementation process, teacher participants in a study conducted by Richman and colleagues (2019) responded overwhelmingly that they appreciated the opportunity to work with educators from surrounding schools and collaborate with others to learn new strategies and create new learning experiences. These teachers also received additional training over time and were given support to integrate literacy standards into their lessons (Richman et al, 2019). The current study and others have demonstrated that teachers value professional development and make efforts to implement new strategies into their instruction; however, it is imperative that the training meet teacher's needs and consider adult learning styles (Martin et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…While teachers in the current study were frustrated by a strict compliance model through the implementation process, teacher participants in a study conducted by Richman and colleagues (2019) responded overwhelmingly that they appreciated the opportunity to work with educators from surrounding schools and collaborate with others to learn new strategies and create new learning experiences. These teachers also received additional training over time and were given support to integrate literacy standards into their lessons (Richman et al, 2019). The current study and others have demonstrated that teachers value professional development and make efforts to implement new strategies into their instruction; however, it is imperative that the training meet teacher's needs and consider adult learning styles (Martin et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, Greenleaf and colleagues (2018) found that without additional interventions, teachers have difficulty integrating literacy into content instruction. Another study has shown that teachers feel their work is enhanced when they are permitted to collaborate with other educators to learn new strategies and create lesson plans (Richman et al, 2019). Allowing teachers time to collaborate as a part of literacy professional development may address the finding of the current study that teachers lacked confidence in their ability to implement literacy strategies in their content-area classrooms and felt disengaged during the professional development sessions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…With the implementation of science standards (NGSS) for the next generation, many prior studies agreed on the significance of providing science teachers with the knowledge and skills necessary to activate the standards in the classroom and their effectiveness. Laxton (2016); Abdel-Karim (2017); Al Rawashdeh (2018); Al Abous et al (2019); Afifi (2019); Akella (2016); Richman et al (2019); Al-Ahmed and Al-Muqbil (2016) and Morales (2016) claimed that science teachers require training and support to comprehend science and geometry standards and their implementation in the semester. Al-Juhni (2020) advocates studying in-service science teachers' requirements and providing NGSS-aligned professional development.…”
Section: Research Problemmentioning
confidence: 99%
“…It means teachers must accept the diversity of students in their class. In addition, it is important for students to use their learning style abilities during the learning process, whereas the teacher should use many methods of teaching (Richman, Haines, & Fello, 2011) and communicating collaboratively during the learning process (Agyekum, 2019). Teachers must be creative to provide teaching materials and learning media (Buabeng, Aquinas Ossei-Anto, & Ampiah, 2014).…”
Section: Introductionmentioning
confidence: 99%